Evaluation of Heat Resistance Characteristics of Fibrous Material for Cold Weather Application - Mithil Bangera; Yash Chavan; Shital Patel; Vinayak Patil (Mechanics of Advanced Composite Structures)
The denier, cross-section, mass density, porosity, and depth of the nonwovens are the nonwovens' physical characteristics that depend on the thermally resistant layer. In this study, we use solid and hollow polyester fibers of various deniers to attempt to optimize these factors for extreme bulk nonwovens. An analysis of contributions has been done to determine the importance of thickness, spatial density, fiber fineness, and form. Better thermal insulation is provided by finer fibers. Nonwovens have a relatively high porosity, and their thermal resistance is particularly low for the lighter and thinner varieties. Thinner and lighter extreme cold-weather apparel is best made from hollow, finer fibers because of their higher thermal insulation. For any studied solid fiber nonwoven with constant thickness, the intrinsic thermal insulation of the nonwoven decreases with an increase in areal density. For 15 mm thick nonwoven, the maximum thermal insulation of 0.4522 m2K/W is obtained for nonwoven with an areal density of 100 g/m2 with 4 denier polyester solid fiber, and the minimum thermal insulation of 0.305 m2K/W is obtained for nonwoven with an areal density of 300 g/m2 with 10 denier polyester solid fiber. The same trends are obtained for nonwovens with thicknesses of 10 mm and 5 mm.